EPIDEMIOLOGY OF TESTICULAR CANCER - Jalolov, Oybek; Mamarasulova, Dilfuzakhon (Medical science of Uzbekistan, 2025)
This review article, devoted to the study of the epidemiology of testicular tumors, presents the analysis of global statistics on oncological diseases, collected from the materials of the World Health Organization (WHO), especially from the International Agency for Research on Cancer, as well as from the GLOBOCAN database. The article highlights the key trends in the incidence of disease and survival of patients with testicular cancer in various regions, including the countries of America, Western, Eastern and Central Europe, as well as the states of the Middle East and East Asia, Southeast and Central Asia. In parallel, statistical data are provided for the CIS countries. Particular attention is paid to the prevalence of this pathology in the Republic of Uzbekistan. Further, testicular cancer is considered in the light of the etiopathogenesis of carcinogenesis. The risks associated with the development of this disease have various aspects, but are united by a common pathogenetic mechanism: long-term hormonal imbalance in the male body, as well as hereditary and genetic factors, such as a personal or family history of testicular cancer and the presence of hereditary mutations. In addition, a link between ethnicity and the incidence of testicular cancer is highlighted, which emphasizes the importance of taking these factors into account in further research.